The The relationship between sedentary lifestyle, fruit and vegetable consumption, and nutritional status of female students in the dormitory of Universitas Andalas. - Fanesa, Algia Amia; Diana, Fivi Melva; Elda, Frima (Nutrición Clínica y Dietética Hospitalaria, 2024)
Introduction Indonesia is currently experiencing a triple burden of malnutriton, namely underweight, overweight, and micronutrient deficiencies, especially anemia. The purpose of the study was to determine the relationship of breakfast habits, fruit and vegetable consumption and sedentary behavior with the nutritional status of female students in the university dormitory andalas. Methode Research with crossectional design. The population is female students who live in the Andalas University dormitory in 2023. The sample was 124 female students living in the Andalas University dormitory, which was selected by simple random sampling technique. Nutritional status data calculated IMT, food intake data obtained through interviews semi quantitative food frequency questionnaire (SQ-FFQ) technique. Data processing with Chi Square test 95% confidence degree (α<0.05). Result The results showed that the characteristics of respondents in the normal nutritional status category were 78 people (62.9%), good breakfast habits were 56 people (45.2%), the average consumption of fruits and vegetables per month was sufficient as many as 45 people (36.3%), and high sedentary behavior was 80 people (64.5%) and the types of vegetables and fruits most consumed by respondents per month were cucumber (63.7%), and papaya (59.7%). There is a significant relationship between breakfast habits and nutritional status (p<0.05) .There is no significant relationship between fruit and vegetable consumption and sedentary behavior with nutritional status (p>0.05). Conclusion This study is that there is a significant relationship between breakfast habits and nutritional status. There is no significant relationship between fruit and vegetable consumption and sedentary behavior with nutritional status.